The impact of a growth mindset on high school students’ learning subjective well-being: the serial mediation role of achievement motivation and grit - Zhao, Wei; Shi, Xiang; Jin, Mingfei; Li, Yangyang; Liang, Chen; Ji, Yilong; Cao, Jiaxuan; Oubibi, Mohamed; Li, Xiaolin; Tian, Yuan (Frontiers in Psychology, 2024)
Purpose: The learning subjective well-being of high school students has significant value for their academic achievement and future life development. Growth mindset is one of the key factors affecting the learning subjective well-being of high school student. However, research on the mechanism by which growth mindset affects learning subjective well-being is still relatively limited. Therefore, the study aims to investigate the impact of growth mindset on the learning subjective well-being of high school students, as well as the role that achievement motivation and grit play as serial mediators in this relationship. Methods: This study employed a convenience sampling method to select 708 high school students from Chinese public high schools as participants. The research utilized the Growth Mindset Scale, Achievement Motivation Scale, Grit Scale, and the Learning Subjective Well-being Questionnaire for High School Students to collect data. All data were analyzed using SPSS 26.0, employing Model 6 from Hayes' SPSS PROCESS macro to test the serial mediation model. Results: Our results found that (1) High school students’ growth mindset positively predicted their learning subjective well-being. (2) Achievement motivation played a mediating role between growth mindset and learning subjective well-being among high school students. (3) Grit acted as a mediator between learning subjective well-being and growth mindset among high school students. (4) Achievement motivation and grit served as serial mediators between growth mindset and learning subjective well-being among high school students. Conclusion: Growth mindset can influence the learning subjective well-being of high school students through achievement motivation and grit. Educators can enhance the learning subjective well-being of high school students by implementing intervention strategies that foster growth mindset, achievement motivation, and grit.